2022
DOI: 10.3389/fphar.2022.1012265
|View full text |Cite
|
Sign up to set email alerts
|

Traditional uses, phytochemical, pharmacology, quality control and modern applications of two important Chinese medicines from Rosa laevigata Michx.: A review

Abstract: Rosa laevigata Michx. is an ethnic medicine that have strong biological activities used in the traditional medicine system for the treatment of diabetes, nephropathy, myocardial damage, oxidative damage, liver damage and so on. Currently, The Chinese herb R. laevigata Michx. can be divided into two important medicines: Fructus R. laevigata and Radix R. laevigata, from which approximately 148 chemical components have been isolated, including flavonoids, lignans, polyphenols, steroids, triterpenoids, tannins as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…This situation mirrors the one observed with triterpenes. In D. oxyodonta , all detected triterpenes belonged to the ursane type, a common triterpenoid found in various members of the Rosaceae family [ 19 , 50 , 51 ]. Consequently, this triterpenoid type cannot serve as a distinguishing criterion for chemodiversity within the Dryas genus.…”
Section: Resultsmentioning
confidence: 99%
“…This situation mirrors the one observed with triterpenes. In D. oxyodonta , all detected triterpenes belonged to the ursane type, a common triterpenoid found in various members of the Rosaceae family [ 19 , 50 , 51 ]. Consequently, this triterpenoid type cannot serve as a distinguishing criterion for chemodiversity within the Dryas genus.…”
Section: Resultsmentioning
confidence: 99%
“…NMR spectroscopy played a crucial role in determining the type of glycosyl residues, substitution site, and sequence. 1 H NMR was used to interpret the conformation of the glycosidic bonds. In the 1 H NMR spectrum (Figure 4A), the signals of RLPa-2 in 1 H NMR ranged from 3 ppm to 6 ppm.…”
Section: Nmr Analysis Of Rlpa-2mentioning
confidence: 99%
“…Rosa laevigata Michx, the dried mature pyriform fruit of the Rosaceae plant, is widely used as a medicinal and edible plant in China [1]. R. laevigata is recognized as a health food resource by the Chinese Ministry of Health, and served as a medicine for the spleen and for relieving diarrhea in Traditional Chinese Medicine (TCM) approximately 1000 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…is a traditional Chinese herbal medicine. Numerous studies have confirmed its antioxidant, anti-inflammatory, and renoprotective effects [ 11 ]. The total flavonoids of Rosa laevigata Michx.…”
Section: Introductionmentioning
confidence: 99%